An investigation of the relative age effect amongst Olympic athletes - O`Neill, K. S.; Cotton, W. G.; Palomares Cuadros, J.; O`Connor, D. (Talent Development & Excellence, 2016)
This study compared birth date distributions of all Olympians in the 2004, 2008 and 2012 Australian and Spanish teams (n =1733) to investigate if a RAE existed within and between nations. Official websites including the International Olympic Committee (IOC), as well as other international, national and state sporting bodies and institutes both in Australia and Spain were utilized for the collection of athlete biographical data. Data were collected for variables including gender, sport, birth date, Games placing, and junior international representation. Chi square analyses and odds-ratios determined a RAE (p <.05) was present amongst Spanish female Olympians and all team sports participants from both nations. No RAE was found amongst junior international competitors or when comparing medalists, finalists and non-finalists.